Prognostic Significance of D-dimer Levels in Predicting Severity and Mortality in COVID-19 Patients: A Comprehensive Analysis - Chawda, Niraj; Jain, Suresh; Solanki, Bhagirath; Sonkar, Chetan; Arora, Simran; Shah, Sukruti; Tejani, Vtrag; Chawla, Jyot Kaur; Chaudhari, Mukesh; Chaudhari, Ravi; Bhattacharya, Amal Kumar (Disease and Health: Research Developments Vol. 3, 2025)
Aim and Objective: The study aims to evaluate the relationship between D-dimer levels and COVID-19 severity and mortality. Materials and Methods: The study retrospectively analysed the patients (Age about \(\ge\)16 years) having confirmed the diagnosis of COVID-19 along with or without comorbid conditions. Pathological and radiological characteristics of 2087 consecutive cases of COVID-19 in Parul Sevashram Hospital, Vadodara, Gujarat, from March 2021 to July 2022. Correlations of D-dimer level of COVID-19 patients upon admission with disease severity and in-hospital mortality were analyzed accordingly. Graphically MS-Excel with median values were used. Results: 2087 patients having positive RT-PCR and confirmed diagnosis of COVID-19 were included upon hospital admission. Whereas 65.78% (n= 1373) were male and 34.21% (n= 714) were female. The mean age was 52\(±\) 4 years. 319 patients died during above said period and overall, the in-hospital mortality rate was 15.28%. Initially, patients were kept on NIV and then shifted to a ventilator based on Spo2 level and continued monitoring. Additionally, 6.08 % (n=127) of patients were on BIPEP and OBPEP and all died with a 100% death ratio. None of the intubated patients (5.60 %, n= 117) were survived. The median elevated D-dimer level was 600.5 ng/ml throughout the study. 81.5 % (n= 1701) patients were found to have elevated D-Dimer levels, and 19.5 % (n= 386) patients were within the normal range. The median D-dimer level in non-survivors (15.29%) was significantly higher than in survivors (84.71%, n = 1768, RR 24.69%). Furthermore, the disease activity was higher in the overhead D-dimer level group demonstrated to have anticipating value in differentiating disease severity along with high ESR level, hs-CRP and the fibrinogen level was also upraised indicating the seriousness of the disease. Conclusion: It was concluded that D-dimer level was routinely uplifted in patients with COVID-19 disease and significantly matched up with the severity of the disease. D-dimer is a significant definitive prognostic first-line marker with twice as high on admission than normal range in COVID-19 and indicates the seriousness of disease.